Improving Mathematics Reasoning Ability of Junior High School Students Using the Learning Star with a Questions Model - Ode Samura, Asri; ., Alfian; Noho, Mubin (KnE Social Sciences, 2024)
This study examines the differences in increasing mathematical reasoning abilities using the Learning start with a question learning model and conventional learning. The research method is quantitative by way of experimental pretest-posttest control group design, which extends the one-group pretest-posttest design in two ways: a second group is added, called the comparison or control group; samples were placed randomly in each group of 83 people. The instrument used is an essay test; the questions are set in the form of mathematical reasoning abilities. Data were analyzed using inferential statistics with an independent sample t-test. The research results obtained are: The application of the LSQ learning model, most students, can solve mathematical reasoning questions correctly. The average score of students who follow the LSQ learning model is higher than the average value of students who take conventional learning; The results of the t-test explained that students who studied using the LSQ model and students who used conventional learning had significantly different improvements in their mathematical reasoning abilities. Students who learn to use the LSQ model increase their reasoning abilities more than the students who study using the conventional model. Keywords: junior high school, learning star with a questions model, mathematics reasoning ability, student